Determining The Effects Of New Technology On Room-And-Pillar Productivity (658bab9b-718b-480d-8ecf-0d3b5ab4664f) - C. J. Johnson (Society for Mining, Metallurgy & Exploration, 1988)
As the U.S. coal industry moves into the next century, it is becoming more apparent that the effective application of new technology is the only way it can remain competitive in the energy marketplace. Examples of this emphasis are with us today in such diverse areas as face-ventilation and excavation-equipment applications. The focus of this new technology is directed toward improvements in health and safety, cost control, and productivity. Room-and-pillar mining accounts for approximately 80% of the nation's underground coal production; this percentage is not expected to decrease markedly in the near future. As such, this paper analyzes the impacts of the changing technological climate on future room-and-pillar operations by comparing a base-case section (current) to three scenarios incorporating new or emerging technology. A microcomputer-based comparative analysis will reflect the changes in section production and costs.